Profile of the antibiotics prescribing of out patiens at the private hospital in Selangor in the period of October to December 2004 - Riswaka Sudjaswadi; Aslina Ashaari (Indonesian Journal of Pharmacy, 2006)
Observation of the antibiotics prescribing of out-patients was carried out by collecting retrospectively all of the prescription received in the period of October to December 2004. Percentage of antibiotics use were obtained from the data. Kinds of the most frequently prescribed antibiotics, percentage of antibiotics prescribed in patent/generic name, and percentage of antibiotics prescribed listed in the hospital formularium, also obtained fromthe data.The results shown that prescribed antibiotics reached 19,54%. The most frequently prescribed were beta lactam derivatives about 58,16%. The ones were prescribed in the patent name about 93,71%, whilst in generic name were 6,29%.Based on the prescribing indikator, the use of antibiotics were lower than 22,70%, which were lower than the lowest value of the WHO observation. That could be stated that was a rational drug use. There were also supported data that all prescribed antibiotics in the hospital formularium list.The prescribing in the generic name was very small.Key words : antibiotics prescribing, prescribing indicator, out-patien